Dynamic multidimensional platform - Bajraszewski, Adam; Markovic, Stefan (My University, 2019)
The project is to be carried out to reach places such as caves, mountain peaks, or other places without exposing a driver or pilot to danger. The purpose is to try to make a platform that, intelligently, moves around in these environments. This is an area where there is potential for improvement and therefore became the choice of this project. The goals for the project were implemented successfully into the platform. The platform’s design was successfully made to transform into the three phases and have implemented ground-borne movements. The three phases are Ground-, air, and water-borne. The design also had implemented symbolic protection shields for the propellers. Wireless communication was implemented. The project mainly focused on the ground-borne phase and movements, while the rest of the phases symbolizes the purpose of this project, which intelligently, move in any terrain or direction. This can be done by allowing the platform to transform into the most efficient of the three phases, corresponding to the challenge it will face. The platform’s potential is more significant than just the three previously mentioned phases.
Keywords: Dynamic platform; multidimensional platform